Pengaruh Perubahan Pelaporan Surat Pemberitahuan (SPT) Tahunan dari Manual ke Elektronik (E-Filing) bagi Efesiensi Administrasi di Indonesia - Rizky Hairiana; Lia Amelia; Atiqah Amalya Azzahra; Ali Murthado Emzaed (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the impact of the transition from manual to electronic (e-Filing) annual tax return (SPT) reporting on the efficiency of tax administration in Indonesia. Indonesia adopts a self-assessment system, granting taxpayers full trust to report and calculate their own tax obligations. However, manual SPT reporting often leads to challenges such as slow processes, human error risks, and high administrative burdens. To address these issues, the government has implemented an electronic filing system (e-Filing) as part of its tax service modernization efforts. This research employs a qualitative library research method by reviewing literature, regulations, and previous relevant studies. The findings indicate that e-Filing significantly enhances administrative efficiency, accelerates processes, reduces operational costs, and improves data accuracy and security. The implications of this research highlight the importance of optimizing socialization, training, and further development of the e-Filing system to encourage more taxpayers to shift to electronic reporting, thereby fostering a more modern, transparent, and accountable tax administration.